2007
DOI: 10.1111/j.1600-0501.2006.01309.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone healing at implants with a fluoride‐modified surface: an experimental study in dogs

Abstract: It is suggested that the fluoride-modified implant surface promotes osseointegration in the early phase of healing following implant installation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
144
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(161 citation statements)
references
References 17 publications
10
144
0
5
Order By: Relevance
“…Titanium has long been considered a stable material for chemical agents owing to its passive state film, but it is possible to change the oxidized titanium surface through exposure to high temperature and strong acid or alkali solutions 14,15) . Recent studies that showed the use of hydrofluoric acid at low concentrations to modify titanium dioxide surfaces revealed increased bone-to-implant contact, enhanced removal-torque, pull-out forces, and differentiation of mesenchymal stem cells [16][17][18] . Acidic fluoride solutions have also been observed to corrode commercially pure titanium and its alloys [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Titanium has long been considered a stable material for chemical agents owing to its passive state film, but it is possible to change the oxidized titanium surface through exposure to high temperature and strong acid or alkali solutions 14,15) . Recent studies that showed the use of hydrofluoric acid at low concentrations to modify titanium dioxide surfaces revealed increased bone-to-implant contact, enhanced removal-torque, pull-out forces, and differentiation of mesenchymal stem cells [16][17][18] . Acidic fluoride solutions have also been observed to corrode commercially pure titanium and its alloys [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation in H 2 O 2 /0.1 M HCl at 80 ∘ C resulted in a good adhesion of arginine-glycine-aspartic acid peptides as well as the calcified matrix formation of rat bone marrow stromal cells [72]. Several studies demonstrated the ability of HF acid, when treated on TiO 2 grit-blasted Ti implants, to enhance the osteoinductive function, differentiation from mesenchymal stem cells into osteoblasts, and early osseointegration [30,35,73,74] …”
Section: Acid Oxidation or Peroxidationmentioning
confidence: 99%
“…The carbon compounds adhering to the titanium surface at the time of placement of the implant are an important factor in determining early adhesion of osteoblast cells to the titanium surface 16) . However, it is not possible to control the accumulation of organic matter during production of titanium implants 10,32) . Other reported methods of managing carbon compound adhesion are ultraviolet treatment 33) , storage in saline solution 34) , and gamma-ray irradiation 35) .…”
Section: Push-in Testmentioning
confidence: 99%